Searching for dark matter with CRESST - Kraus, H; Angloher, G; Bauer, M; Bavykina, I; Bento, A; Brown, A; Bucci, C; Ciemniak, C; Coppi, C; Deuter, G; Von Feilitzsch, F; Hauff, D; et al. (2009)
The CRESST II experiment is a dark matter search using cryogenic phonon-scintillation detectors, aiming to detect WIMP dark matter particle interactions. The detector consists of individual, modular and scintillating (CaWO4 or ZnWO4) target crystals, each equipped with a phonon sensor for precise determination of the energy deposited in the crystals. Each module is further equipped with a separate cryogenic scintillation light detector, allowing event-by-event background discrimination. An extended commissioning run during 2007 has set an upper limit on theWIMP-nucleon scattering cross section. Attention is currently focussed on the interpretation of a few remaining nuclear recoils candidate events.